High mobility group box 1 protein in the central nervous system (Journal of Medical Science, 2014)
High-mobility group box 1 protein (HMGB1) is a multifunctional protein originally identified as a nuclear transcription modifier. Two pathways are leading to HMGB1 release to the extracellular space i.e. active secretion triggered by noxious stimulation and passive leakage due to necrotic membrane damage. Binding with receptors for advanced glycation end products (RAGE) as well as Toll-like receptor 2 (TLR2) and TLR4 leads to nuclear factor ?B (NF-?B) activation and proinflammatory reaction in target cells. Secretion of cytokines, upregulation of adhesion molecules and chemoattraction are triggered by the extracellular HMGB1. Such ubiquitous and numerous protein plays a role in pathogenesis of many common diseases like sepsis, rheumatoid arthritis and pneumonia. Central nervous system (CNS) disorders are also mediated by HMGB1. Multiple studies highlight pivotal role of HMGB1 in acute pathologies of CNS like cerebral ischemia, aneurysmal subarachnoid hemorrhage as well as chronic degenerative disorders such as Alzheimer’s disease and multiple sclerosis. Wide range of HMGB1 antagonists are currently investigated as novel therapeutic agents in sepsis, colitis and stroke. This review article provides basic information about HMGB1 protein and its role in the pathogenesis of CNS diseases.